Kajian Uji Kualitas Sumber Air untuk Pemenuhan Kebutuhan Air Bersih di Daerah Rawa yang Berkelanjutan - Imam Suprayogi; Manyuk Fauzi; Ferry Fatnanta; Alfian Alfian; Ela Fitriana; Aras Mulyadi; Effendi Sianipar (Universitas Riau, 2023)
Siak Regency consists of plains and hills with an average soil composition consisting of podzolic red yellow rocks and alluvium and organosol soil and humus gley in the form of swamps or wet gley. United States Department of Agriculture (USDA) that Podsolic Red Yellow (PMK) soil is a soil formed due to too low temperature and very high rainfall and is an ancient mineral soil type with a reddish or yellowish color. This podzolic soil color indicates relatively low soil productivity due to leaching. While the red and yellow soil colors are caused by rusty iron and lumps of aluminum that decompose and undergo weathering. Clay minerals in this soil are dominated by compounds containing silicon, oxygen, and some metals, which have implications for water quality. The purpose of this research is to test water quality to support the fulfillment of sustainable clean water needs in the Swamp Area in Rempak Village, Siak District, Siak Regency, Riau Provonce. The approach method used is Permenkes No. 492/Menkes/IV/2010.The data needed for this research is to use primary data by taking samples of rainwater, well water, and raw water from the Siak river by researchers directly on March 16, 2022. The main results of the research stated that the quality of rainwater was ranked first to support the policies of the National Development Planning Agency towards a just and prosperous Indonesia in 2045 which has mandated the importance of water security to support strategic sectors, disaster prevention, and improvement of community welfare through construction of rainwater harvesting buildings.